“Monitoring inflammatory, immune system mediators, and mitochondrial changes related to brain metabolism during space flight” - Tocci, Darcy; Ducai, Tomas; Stoute, C. A. Barry; Hopkins, Gabrielle; Sabbir, Mohammad G.; Beheshti, Afshin; Albensi, Benedict C. (Frontiers in Immunology, 2024)
The possibility of impaired cognitive function during deep space flight missions or while living on a Martian colony is a critical point of concern and pleads for further research. In addition, a fundamental gap exists both in our understanding and application of countermeasures for the consequences of long duration space travel and/or living in an extreme environment such as on the Moon or Mars. Previous studies, while heavily analyzing pre-and post-flight conditions, mostly fail to appreciate the cognitive stressors associated with space radiation, microgravity, confinement, hostile or closed environments, and the long distances from earth. A specific understanding of factors that affect cognition as well as structural and/or physiological changes in the brains of those on a space mission in addition to new countermeasures should result in improved health of our astronauts and reduce risks. At the core of cognitive changes are mechanisms we typically associate with aging, such as inflammatory responses, changes in brain metabolism, depression, and memory impairments. In fact, space flight appears to accelerate aging.In this review, we will discuss the importance of monitoring inflammatory and immune system mediators such as nuclear factor kappa B (NF-B), and mitochondrial changes related to brain metabolism. We conclude with our recommended countermeasures that include pharmacological, metabolic, and nutritional considerations for the risks on cognition during space missions.